2020
DOI: 10.1049/iet-nbt.2019.0224
|View full text |Cite
|
Sign up to set email alerts
|

Silver nanorods induced oxidative stress and chromosomal aberrations in the Allium cepa model

Abstract: The production of different size and shape silver nanoparticles (AgNPs) has increased considerably in recent years due to several commercial and biological applications. Here, rod-shaped AgNPs (SNRs) were prepared using the microwaveassisted method and characterised by ultraviolet-visible spectroscopy, and transmission electron microscopy analysis. The present study aims to investigate the cyto-genotoxic effect of various concentrations (5, 10, and 15 µM) of SNRs using Allium cepa model. As a result, concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…Durairaj, Roy, Chandrasekaran, Krishnan, and Mukherjee (2020) investigated the cell viability and different ROS assays of various concentrations (5, 10, and 15 μM) of Ag NRs using Allium cepa . They found that exposure to Ag NRs decreased in the mitotic index and an increased in the chromosomal aberrations such as chromosome break, disturbed metaphase, and anaphase bridge.…”
Section: Non‐magnetic Metallic Nanomaterialsmentioning
confidence: 99%
“…Durairaj, Roy, Chandrasekaran, Krishnan, and Mukherjee (2020) investigated the cell viability and different ROS assays of various concentrations (5, 10, and 15 μM) of Ag NRs using Allium cepa . They found that exposure to Ag NRs decreased in the mitotic index and an increased in the chromosomal aberrations such as chromosome break, disturbed metaphase, and anaphase bridge.…”
Section: Non‐magnetic Metallic Nanomaterialsmentioning
confidence: 99%
“…1c). Stickiness, a chromatid type abnormality, is arisen from the inappropriate folding of inner chromatins into chromatids or depolymerization of chromosomes 21 . It is considered to be an irreversible chromosomal abnormality and usually result in death of the cells 35 .…”
Section: Resultsmentioning
confidence: 99%